Studi Pendahuluan Ekstraksi Bertingkat Minyak Biji Mangga Arumanis (Mangifera Indica) Menggunalan Pelarut N-Heksan dan Etanol - Masúd, Fajriyati; Puspitasari, Puspitasari (Politeknik Negeri Ujung Pandang, 2017)
Mango seeds containing oil of about 20-37%, is one source of vegetable oil that has not been touched. Mango seed oil contains polyphenols, so the potential is developed as a functional food. Mango seed oil contains high solid, it can be developed into a product resembling spreadable margarine. The aim of this study was to determine the ratio of solvent, temperature, and time is optimum for extracting mango seed oil. Mango seed oil has been extracted by multistage extraction with hexane and ethanol. Extraction process was performed using reflux method at 30, 35, 40, 45, 50, 55, 60°C, for 1, 2, 3, 4, 5, 6 hours, with solvent ratio of 1: 2, 1: 3, 1: 4, 1: 5, 1: 6. The results showed that the ratio of solvent 1: 4, 50°C for 4 hours is the best condition for extracting mango seed oil by multistage extraction using n-hexane and ethanol.